UPAYA PEMUDA KRISTEN DALAM MENJALANKAN PERIBADATAN DI GEREJA DESA PADA MASA PANDEMI COVID-19 - Wardi (Diegesis : Jurnal Teologi, 2021)
The COVID-19 pandemic that is still spreading to this day has closed direct services in the church. Not only churches located in urban areas, but churches located in villages are also not spared the problem of the Covid-19 pandemic. Likewise, the existing Christian youth associations were also temporarily closed for their activities. The purpose of this research is to explore the efforts that can be made by Christian youth, especially in village churches in the face of the Covid-19 pandemic. The research method used is descriptive qualitative to reveal the efforts that can be made by Christian youth in facing the challenges of the covid-19 pandemic. The results showed that Christian youth became the main milestone in carrying out worship in local churches, especially villages, because of significant changes. Therefore, it is necessary to adapt quickly to be able to find the right strategy in carrying out worship at the village church.